CM Speeches for 55th NDC Meeting Volume II 24th July, 2010 Vigyan Bhawan New Delhi - Planning Commission (Planning Commission, 2010)
Macroeconomic Overview, Sectoral Growth and monitorable indicators - The State GSDP has shown more or less, a stable growth rate trend from the 9th Plan period onwards. During the 9th and 10th Plan periods, the State had average GSDP growth rates of 6.6% and 6.5% respectively. The State expectation for the 11th Plan period is 6.4%, against which the State recorded growth rates of 6.4% and 5.9% in the first two years. The fall in growth rate in 2008-09 was in lines with the fall in other parts of the country due to the Global Economic crisis. There is normally a time lag for the national growth cycle to replicate in Arunachal Pradesh and hence, the growth rate in 2009-10 is also likely to be in the range of about 6%.
National Development Council
National Development Council